An Afriat theorem for the collective model of household consumption - Laurens Cherchye; Bram De Rock; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2008)
We provide a nonparametric 'revealed preference' characterization of rational household behavior in terms of the collective consumption model, while accounting for general (possibly non-convex) individual preferences. We establish a Collective Axiom of Revealed Preference (CARP), which provides a necessary and sufficient condition for data consistency with collective rationality. Our main result takes the form of a 'collective' version of the Afriat Theorem for rational behavior in terms of the unitary model. This theorem has some interesting implications. With only a finite set of observations, the nature of consumption externalities (positive or negative) in the intra-household allocation process is non-testable. The same non-testability conclusion holds for privateness (with or without externalities) or publicness of consumption. By contrast, concavity of individual utility functions (representing convex preferences) turns out to be testable. In addition, monotonicity is testable for the model that assumes all household consumption is public.
urn:nbn:de:101:1-20081126681
Keywords: D11; 330; Collective model; consumption; Pareto efficiency; revealed preferences; Afriat theorem; Collective Axiom of Revealed Preferences; Konsumentenverhalten; Privater Haushalt; Haushaltsökonomik; Pareto-Optimum; Offenbarte Präferenzen; Theorie